THE INFLUENCE OF FINANCIAL PERFORMANCE ON THE PROFITABILITY OF SHARIA COMMERCIAL BANK IN INDONESIA - Audina, Mia; Siregar, Pani Akhiruddin; Putri, Alya Saskia; Rahman, Anggi Sartika (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to analyze the influence of financial performance on the profitability of Sharia Commercial Bank in Indonesia. Financial performance indicator with CAR, NPF, and BOPO. The profitability indicator of Sharia Commercial Bank in Indonesia with ROA. This type of research data with secondary data is sourced from the Financial Performance of Sharia Commercial Bank and Business Activities of Sharia Commercial Bank through the publication of Sharia Indonesia Banking Statistic, Financial Services Authority (SPS-OJK). The research sample was taken periodically in the form of monthly data from January 2020 to September 2023. At least, the amount of data that can be further analyzed is 45 data. Sampling technique with simple random sampling. The results of the research are as follows: (1) The estimation model shows an R2 value of 0,983 which represents the value of the coefficient of determination. This means that 98,30% of the dependent variable variation is able to be explained by the independent variable in this model. The remaining 1,70% is explained by other causes that are not included in the model; 2) The regression model on the independent variable simultaneously influence the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (3) This research produced output that CAR, NPF, and BOPO have an influential and are significant on ROA Sharia Commercial Bank in Indonesia.